LEGAL ANALYSIS OF INHERITANCE DISPUTE SETTLEMENT FROM THE PERSPECTIVE OF CIVIL LAW AND CHINESE CUSTOMARY LAW (Study of Decision No. 54/Pdt.G/2020/PN.Mdn Jo Decision No. 22/Pdt/2021/PT MDN Decision Jo No.3539 K/Pdt/2022) - Sitanggang, Yolanda Br; Sitepu, Rungtung; Sembiring, Rosnidar (Jurnal Hukum Replik, 2025)
This research analyzes the resolution of inheritance distribution disputes from the perspective of civil law and Chinese customary law through a case study of Decision No. 54/Pdt.G/2020/PN.Mdn Jo Decision No. 22/Pdt/2021/PT MDN Decision Jo No.3539 K/Pdt/2022. Using normative legal research methods, this study examines the position and rights of heirs between men and women according to the Indonesian Civil Code (KUHPerdata), which is egalitarian with equal distribution as regulated in Article 852, while Chinese customary law gives men a higher position due to their responsibility towards ancestors. The inheritance dispute in this case was resolved through litigation in court because family deliberation did not reach an agreement. The panel of judges decided on equal inheritance distribution (1/3 for each heir) based on the provisions of Article 852 of the Civil Code, ignoring Chinese customary traditions that give a larger portion to male children. This research shows that although the Chinese community can use civil inheritance law, in practice there are still conflicts between customary norms and the applicable positive law